2017
DOI: 10.3390/socsci6030096
|View full text |Cite
|
Sign up to set email alerts
|

Social Network Decay as Potential Recovery from Homelessness: A Mixed Methods Study in Housing First Programming

Abstract: The positive relationship between social support and mental health has been well documented, but individuals experiencing chronic homelessness face serious disruptions to their social networks. Housing First (HF) programming has been shown to improve health and stability of formerly chronically homeless individuals. However, researchers are only just starting to understand the impact HF has on residents’ individual social integration. The purpose of the current study was to describe and understand changes in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 41 publications
2
36
0
Order By: Relevance
“…Previous research has identified relocation as a precipitant of network change (Wrzus et al, 2013;Curley, 2009); prior research also found, as we did here, that family social network members were less likely to be disrupted during relocation. These findings also support those by Golembiewski et al (2017) that the change and constriction of networks may focus and strengthen positive relationships, such as those with family. The network decay found by those authors occurred over the first year in housing; given the nonsignificant trend of network reduction at three months in this study, following persons in PSH over a longer period of time may demonstrate similar network decay.…”
Section: Discussionsupporting
confidence: 87%
“…Previous research has identified relocation as a precipitant of network change (Wrzus et al, 2013;Curley, 2009); prior research also found, as we did here, that family social network members were less likely to be disrupted during relocation. These findings also support those by Golembiewski et al (2017) that the change and constriction of networks may focus and strengthen positive relationships, such as those with family. The network decay found by those authors occurred over the first year in housing; given the nonsignificant trend of network reduction at three months in this study, following persons in PSH over a longer period of time may demonstrate similar network decay.…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, building social support is not merely about adding to the social network; research suggests that the quality of social relationships is important to health, particularly for homeless women, suggesting the importance of having low-conflict social relationships [44,48]. Finally, the effect of individual circumstances (e.g., living in sheltered versus unsheltered settings, transition to more permanent housing, or caregivers for children) should be considered in interventions to build and maintain social support for this population, knowing that circumstances, and a change in them, can be disruptive to extant support networks, requiring reassessment and additional resource/resiliency planning [49][50][51][52]. Ultimately, such efforts to build supportive social networks may have positive effects on mental and physical manifestations of poor HRQoL among individuals experiencing homelessness.…”
Section: Discussionmentioning
confidence: 99%
“…Works on loneliness in individuals experiencing homelessness have reported high levels of interpersonal isolation and self-alienation as a consequence of a situation of constant struggle for daily survival, violence, victimization, abuse, drug consumption, and social stigma [ 8 , 9 ]. All this has contributed to the generalized perception that individuals experiencing homelessness are lonely people isolated from the rest of society [ 10 ]. However, in the last 10 years, there have been substantial changes in humans’ communicative and relational dimensions.…”
Section: Introductionmentioning
confidence: 99%